Effective transboundary aquifer areas between Mexico and the United States: A border-wide approach - Rosario Sanchez; Duncan Kikoyo; Luna Yang (Journal of Hydrology: Regional Studies)
Study Region: This research is situated in the U.S-Mexico border region. It encompasses the geographical extension of the 28 transboundary aquifers located across the ten border states between the two countries. Study Focus: This study aims to identify regions within the hydrogeological units shared across the U.S.-Mexico border that could be in a vulnerable condition due to groundwater overexploitation on either side of the border. The Effective Transboundary Aquifer Area (ETAA) approach attempts to represent those effective geographical areas of groundwater production within the geological boundaries of the aquifer, to prioritize vulnerable areas at a more refined and local scale. To identify ETAAs, this study uses well density well depth data to portray depth contours as a proxy for potential impacts of groundwater flows at transboundary level. New Hydrological Insights: For planning and management purposes at binational scale and considering the constraints on data and research on transboundary aquifers, the ETAAs provide a more feasible and useful approach to assess the conditions of a shared resource at a more “localized” scale. This approach facilitates the integration of stakeholders’ perspectives and specific needs of the communities that overlay the ETAA. Results show the location and extension of the ETAAs across the complete U.S.-Mexico border identifying the most vulnerable and highly groundwater-dependent regions.